2021
DOI: 10.9734/jpri/2021/v33i60b34877
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Festivals on Weight Gain

Abstract: Obesity is on the rise, and the fundamental causes of this development are still a source of debate. The extent of holiday weight gain and its relation to annual weight gain was recently investigated. The study aims to review the literature to ascertain the consequences of holidays on weight gain. In India, holidays during summer vacation and festive show a significant rise in weight gain, whereas in USA UK, the 6-week long winter vacation shows a significant rise in weight gain. The COVID-19 Millions of peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…This finding is consistent with a previous study, showed a significant rise in weight gain during COVID-19 among individuals who had a 6-week long winter vacation in the USA and UK. 21 However, it is important to note that the heterogeneous findings suggest that study designs, target population, frequency, season, and duration of TC exercise are all important factors in detecting significant clinically relevant effects. [22][23][24] It is important to consider the impact of various factors on the results of this study, such as a small sample size, short duration of intervention, and differences in the participants' baseline characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a previous study, showed a significant rise in weight gain during COVID-19 among individuals who had a 6-week long winter vacation in the USA and UK. 21 However, it is important to note that the heterogeneous findings suggest that study designs, target population, frequency, season, and duration of TC exercise are all important factors in detecting significant clinically relevant effects. [22][23][24] It is important to consider the impact of various factors on the results of this study, such as a small sample size, short duration of intervention, and differences in the participants' baseline characteristics.…”
Section: Discussionmentioning
confidence: 99%